Analisis Upaya Dinas Pemberdayaan Perempuan dan Perlindungan Anak dalam Pencegahan Perdagangan Perempuan dan Anak di Kota Kupang - Angel Algin Medah; Jacob Wadu; Delila Anggelina Nahak Seran (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study analyzes the efforts of the Kupang City Office of Women’s Empowerment and Child Protection (DP3A) to prevent trafficking in women and children. It employed a descriptive qualitative approach involving 12 informants selected through purposive sampling. Data were collected through interviews, observation, and documentation and analyzed through data reduction, data presentation, and conclusion drawing. Data validity was ensured through source, technique, and time triangulation. The findings indicate that prevention was implemented through four dimensions. Preventive efforts included public education, cross-sector collaboration, supervision, and media utilization. Preservative efforts involved task forces in 51 urban villages, monitoring, and evaluation. Curative efforts comprised victim assistance, counseling, rehabilitation, legal support, and social reintegration. Adaptive efforts were undertaken by utilizing social media and adjusting collaboration to emerging digital trafficking practices. However, implementation remained constrained by limited funding and personnel, weak community and parental supervision, inadequate digital communication, the absence of permanent psychologists, a shortage of social workers, and the lack of specific innovations addressing digital trafficking. Therefore, stronger institutional capacity, professional personnel, measurable program evaluation, and integrated digital prevention strategies are required.